Mitigated phase transition during first cycle of a Li-rich layered cathode studied by in operando synchrotron X-ray powder diffraction - Song, B; Day, S; Sui, T; Lu, L; Tang, C; Korsunsky, A (Royal Society of Chemistry, 2016)
In operando synchrotron X-ray powder diffraction (SXPD) studies were conducted to investigate the phase transition of Li-rich Li(Li0.2Ni0.13Mn0.54Co0.13)O2 and Cr-doped Li(Li0.2Ni0.13Mn0.54Co0.03Cr0.10)O2 cathodes during the first charge/discharge cycle. Crystallographic (lattice parameters) and mechanical (domain size and microstrain) information was collected from SXPD full pattern refinement. It was found that Cr substitution at Co-site benefits in suppressing the activation of Li2MnO3 domains upon 1st charge, and thus mitigates the phase transition. As a consequence, Cr-doped layered cathode holds a better reversibility in terms of a full recovery of both lattice parameters and nano-domain size after a whole charge/discharge cycle. The effects of different cycling rates on the structural change were also discussed.